Fixed and fair power allocation in downlink and uplink NOMA: outage probability analysis and bit error rate comparative study - Falloun, Abdelbari; Ait Madi, Abdessalam (Bulletin of Electrical Engineering and Informatics, 2025)
Non-orthogonal multiple access (NOMA) is a crucial technology for upcoming radio access networks since it allows several users to use the same time and frequency resources. It is positioned as a viable option for next-generation communication systems because to its capabilities to increase system capacity and spectrum efficiency. This essay investigates the effects of fair and fixed power allocation (PA) techniques on NOMA systems' uplink and downlink performance. It specifically assesses bit error rate (BER) and outage probability (OP), two crucial performance parameters. The paper provides a thorough comparison of the fixed and fair PA approaches, highlighting the advantages, and disadvantages of each. While fixed PA is easier to deploy, results show that it performs poorly in dynamic situations, increasing BER and OP, particularly for users with less reliable channels. Fair PA, on the other hand, improves system dependability, and user fairness by dynamically allocating power depending on user situations, thus reducing OP and BER. Future wireless networks will benefit greatly from its enhanced spectrum efficiency and up to 78% reduction in outage likelihood. With fair PA's higher flexibility and effectiveness in real-world, varied circumstances, the results underline the significance of selecting appropriate PA techniques for NOMA systems.